„Néger atyafiak”: Emlékezettörténeti epizód a millenniumi ünnepségekről - Bódi, Katalin (Studia Litteraria, 2018)
In the Hungarian cultural memory the festival of the Hungarian Millennium in Budapest was an occasion to celebrate the social and the industrial development of the country which became the coequal partner of Austria after the Austro-Hungarian Compromise of 1867. The festival was similar to a World’s Fair of the era, with many popular spectacles in the City Park of the capital. In my paper I describe a forgotten episode of the festival, notably the exhibit of an African tribe in the zoo of Budapest. By the analysis of the report of the weekly Vasárnapi Ujság (Sunday News) it is possible to demonstrate that the millennial narrative of the modernity and the successful nation is based on a colonial discourse.